Antidepressant use during pregnancy and the risk of developing gestational hypertension: a retrospective cohort study - Neily Zakiyah; Loes F. ter Heijne; Jens H. Bos; Eelko Hak; Maarten J. Postma; Catharina C. M. Schuiling-Veninga (BMC, 2018)
Abstract Background Prior studies reported that exposure to antidepressants during pregnancy may be associated with gestational hypertension. The aim of this study is to assess the association between the use of antidepressants during pregnancy and the risk of developing gestational hypertension. Methods A retrospective cohort study using the prescription database IADB.nl was conducted among nulliparous women with singleton pregnancies between 1994 and 2015 in the Netherlands. Logistic regression analysis was used to estimate odds ratios (OR), adjusted OR (aOR) and their corresponding 95% confidence intervals (95% CI). Gestational hypertension as main outcome measure was defined as at least one dispensed record of an antihypertensive drug (methyldopa, nifedipine, labetalol, ketanserin, nicardipine) after 20 weeks of gestation until 14 days after delivery. Sub-analyses were conducted for class of antidepressant, duration and amount of use of antidepressant (≤30, ≥30 Defined Daily Doses or DDDs), and maternal age. Sensitivity analyses to assess uncertainties were conducted. Results Twenty-eight thousand twenty women were included, of which 539 (1.92%) used antidepressants. The risk of gestational hypertension was doubled for women using antidepressant (aOR 2.00 95% CI 1.28-3.13). Significant associations were also found for the subgroup selective serotonin reuptake inhibitors (SSRIs) (aOR 2.07 95% CI 1.25-3.44), ≥30 DDDs (aOR 2.50 95% CI 1.55-3.99) and maternal age of 30-34 years (aOR 2.59 95% CI 1.35-4.98). Varying the theoretical gestational age showed comparable results. Conclusion Prolonged use of antidepressants during the first 20 weeks of gestation appeared to be associated with an increased risk of developing gestational hypertension. When balancing the benefits and risks of using these drugs during pregnancy, this should be taken into account.